Combination of thermal and dual‐frequency sonication processes for optimum microbiological and antioxidant properties in cherry tomato. Issue 2 (24th November 2019) - Mustapha, Abdullateef Taiye; Zhou, Cunshan; Wahia, Hafida; Sarpong, Frederick; Nasiru, Mustapha Muhammad; Adegbemiga, Yusuf Bashir; Ma, Haile
Abstract: Cherry tomato fruits were treated with three dual‐frequency ultrasound (US) at different temperature and time. The three treatment variables, that is, dual‐frequency US, temperature, and time were optimized with the aid of response surface methodology (RSM). About 20/40 kHz, 52°C, and 6 min were the optimum condition obtained for total bacteria count (TBC, 1.08 log cfu/g), firmness (15.90 N), and total phenolic content (TPC, 34.34 mg GAE/100 g). All the linear relations of the treatment variables showed a significantly negative and positive effect on the TBC and TPC, respectively, while positive significant effects were obtained for some of the relations of the firmness. Hence dual‐frequency sonication is effective for microbial safety and maintaining the quality of cherry tomato. Also, RSM was found to be a useful tool in setting and optimizing the variables responsible for sonication treatment. Practical applications: Thermosonication (ultrasonication and heat) has been applied toward improving the microbial safety and nutritional quality of vegetables and fruit. However, factors such as power, frequency, time, temperature, etc. determine the efficiency of its operation. Controlling these factors is difficult and therefore requires a robust and efficient optimization tool in determining their effects (individual and interactions) on food during treatment. In this study, response surface methodology provides the solution in settling and optimizing the variables for the sonication treatment. Besides, the remarkable result obtained in this work offers an alternative to the combined use of ultrasound and chemical in food industries.